Family influence on internationalization: an analysis of risk acceptance - Goede, Waldir; Floriani, Dinorá Eliete; Furtado Filho, Ademir (Revista de Negócios, 2018)
This article aims to contribute to the literature on family business (FBs), particularly from the perspective of commitment and influence of family on the FB internationalization regarding risk acceptance. Qualitative in nature, the study involved the use of a single longitudinal case study, based on in-depth interviews, storytelling and secondary data. Primary data were collected through semi-structured personal interviews with the company’s board chairman and vice-chairman, commercial director, European director and export manager; and secondary data were obtained using documental and scientific sources. It could be seen that family commitment and ownership influenced the internationalization process due to the proactivity of its European descendant founders, and particularly because in this company studied the process was initiated by a non-family member. However, family participation encourages risk acceptance, since the attachment to the family business creates an eagerness for growth. The findings corroborate the characteristics proposed by the Uppsala School, which claims that internationalization occurs in an unplanned, opportunistic manner, following sequential phases, through incremental learning and via the establishment of networks.